The evolution of Wilde's wit - Gantar, Jure 1964- (Palgrave Macmillan, 2015)
"Oscar Wilde's wit is foundational to his works, from his plays and novels to his self-defense at his trials. Through analysis of Wilde's collection of epigrams, 'Phrases and Philosophies for the Use of the Young, ' Gantar constructs a framework for a systematic analysis of the different aspects of Wilde's wit: the relevance, significance, and cogency of its thought, and the coherence, intensity, and complexity of its expression. This book is a comprehensive account of Oscar Wilde's wit that focuses on discovering reasons for his critical success and ongoing legacy"--